2021
DOI: 10.1007/s00268-021-06202-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Nutritional Status is Predictive of the Survival Outcomes in Patients Undergoing Resection of Stage III Colorectal Cancer

Abstract: Background Preoperative nutritional status is reportedly associated with the clinical outcomes in patients with colorectal cancer (CRC), although it remains inconclusive whether the preoperative nutritional status that may improve after surgery is truly predictive of the survival outcomes of patients with CRC. Methods Clinical records of patients with stage III CRC (n = 821) in whom curative resection had been achieved were retrospectively reviewed and the prognostic impact of nutritional status, determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…we observed a significant increase in the prevalence of malnutrition from hospital admission to discharge. Preoperative CONUT score has previously been correlated with a higher mortality rate [ 22 ]. although not with increased length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…we observed a significant increase in the prevalence of malnutrition from hospital admission to discharge. Preoperative CONUT score has previously been correlated with a higher mortality rate [ 22 ]. although not with increased length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that malnutrition prevalence has been widely reported to reach 15–40% in patients with cancer at the time of diagnosis, and up to 80–90% in advanced cases of the disease ( 8 ). The prevalence of malnutrition in CRC patients also ranged from 45 to 60% ( 9 ) and these rates significantly increased followed by radical surgery ( 10 ). In addition, immune dysfunction or immunosuppression caused by surgery acted as the main inducement of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, tumor resection was found to alter the nutritional state of patients, and postoperative nutritional status in the non-cancer-bearing state more accurately predicted outcomes in patients with Stage III CRC. 28,29 Further studies will be needed to verify these important findings. Third, potential confounders such as KRAS, BRAF, and MSI status were not included in the analyses.…”
Section: Discussionmentioning
confidence: 98%